Whither Pharmacometrics?: Present State and Future Choices. Issue 6 (12th March 2014) - Vicini, P; Smith, B P
<x xml:space="preserve">Abstract</x> The theme of this month's issue of Clinical Pharmacology & Therapeutics is pharmacometrics. When looking back at the early days of pharmacometrics, current contributions to the drug development process look impressive. The questions are whether the original promise is being kept and how the impact can become even greater. Clinical Pharmacology & Therapeutics (2014); 95 6, 567–571. doi:10.1038/clpt.2014.72